Characteristics and Outcomes of Young Patients with First-Ever Ischemic Stroke Compared to Older Patients: The National Acute Stroke ISraeli Registry - Lutski, Miri; Zucker, Inbar; Shohat, Tamy; Tanne, David (Frontiers in Neurology, 2017)
Background: Nationwide data on the clinical profile and outcomes of ischemic stroke in younger adults are still scarce. Our aim was to analyze clinical characteristics and outcomes of young patients with first-ever ischemic stroke compared to older patients. Methods: The National Acute Stroke ISraeli (NASIS) registry is a nationwide prospective hospital-based study performed triennially. Younger adults, aged 50 years and younger, were compared with patients, aged 51-84 years regarding risk factors, clinical presentation, stroke severity, stroke etiology and outcomes. A logistic model for stroke outcome was fitted for each age group. Results: 336 first-ever ischemic strokes were identified among patients aged 50 years and younger and 3,243 among patients 51-84 years. Younger adults had lower rates of traditional vascular risk factors, but 82.7% had at least one of these risk factors. Younger adults were more likely to be male (62.8%), current smokers (47.3%), and to have a family history of stroke (7.4%). They tended to have less common stroke presentation such as sensory disturbances or headache, and were more likely to arrive at the hospital independently by car. The majority of young adults (70%) had a favorable outcome (mRS≤1) at discharge, but 11.7% had poor outcome (mRS>3) and 18.2% had an in-hospital complication. According to a multivariable regression model, in young adults, only baseline stroke severity (NIHSS >5) was associated with poor outcome at discharge (p<0.001); whereas in older adults, stroke severity (p<0.001), female gender (OR=1.35, CI 95% 1.03-1.76), older age (OR=1.08, CI 95% 1.01-1.16), atrial fibrillation (OR=1.62, CI 95% 1.16-2.26) and anterior circulation territory (OR=2.10, CI 95% 1.50-2.94) were all significantly associated with poor outcome. Conclusions: Our findings, in this nationwide registry, demonstrate the relatively high rate of smoking and family history of stroke, and the lower rate of hospital arrival by ambulance among young adults. This calls for increasing awareness to the possibility of stroke among young adults and for better prevention, especially smoking cessation.